Identification and Expression Analysis of an Atypical Alkaline Phosphatase in Emiliania huxleyi - Li, Tangcheng; Guo, Chentao; Zhang, Yaqun; Wang, Cong; Lin, Xin; Lin, Senjie (Frontiers in Microbiology, 2018)
Emiliania huxleyi, a cosmopolitan coccolithophore in the modern ocean, plays an important role in the carbon cycle and local climate feedback as it can form extensive blooms, calcify, and produce dimethylsulfoniopropionate (DMSP) leading to the generation of dimethyl sulfide (DMS) which affects climate when oxidized in the atmosphere. It is known to be able to utilize dissolved organic phosphorus (DOP) by expressing a specific type of alkaline phosphatase (EHAP1) under phosphorus-limited conditions. In this study, we identified a new alkaline phosphatase (EH-PhoAaty) in this species, which we found belongs to the newly classified PhoAaty family. The expression of this atypical phosphatase was up-regulated under P-deplete conditions at both the transcriptional and translational levels, suggesting that E. huxleyi is able to express this AP to cope with phosphorus limitation. Comparative analysis revealed different transcriptional expression dynamics between eh-phoAaty and ehap1, although both genes exhibited inducible expression under phosphate deficiency. In addition, after AP activity was eliminated by using EDTA to chelate metal ions, we found that AP activity was recovered with the supplement of Ca2+ and Zn2+, indicative of the adoption of Ca2+ as the cofactor under Zn-P co-limited conditions, likely a result of adaptation to oceanic environments where Zn2+ is often limiting. Keywords: Emiliania huxleyi, alkaline phosphatase, gene expression, phosphorus limitation, cofactor